EVALUATION OF DISPLACEMENT ON UNSATURATED SOILS IN BANGKOK PLAIN - Sutasinee Intui; Jittiphan Jindawutthiphan; Shinya Inazumi (GEOMATE Journal, 2022)
Chao Phraya River basin is located in the central area of Thailand which has a lot of ground displacement issues due to groundwater pumping. Following the Department of Groundwater Resources (DGR) in Thailand recording data, the groundwater level changed due to water pumping from 1960 until now. In 1997, DGR issued a law regulating the use of groundwater effect to the characteristic of changing groundwater levels. Therefore, the characteristic of groundwater level change was separated into two periods. In the first period, the high groundwater pumping rate led to a rapid decrease in groundwater level at about 27 meters from the ground surface. After DGR issued the law, the pumping ratio decreased and the groundwater level was increased or recovered close to the ground surface. The groundwater level recovery still affected ground displacement. This study focuses on evaluating and predicting ground displacement during groundwater level recovery in the future based on Terzaghi’s theory. The study area considers only zone D (10 to 14 m of soft clay thickness) in the Bangkok clay area. The soil profile and the soil boring log were gathered from the Department of Public Works and Town & Country Planning in Thailand. This study research the ground displacement behavior of the clay layer during groundwater recovery. All data will be used to make a 3D soil profile and calculate to predict ground displacement in the future of the soil layer. The results found that the ground displacement has rebound to the ground surface of every bored hole during the groundwater recovery.